The decline of communism in China legitimacy crisis 1977 - 1989 - Ding, X.L (Cambridge University Press, 2006)
This book begins by asking, How could it be that under the Deng regime, when the People's Republic of China experienced its greatest economic prosperity, the largest and most tragically concluded popular protest took place? To answer this question the author examines, from the viewpoint of a participant, the relations between the Communist political elite and the largely anti-Communist intellectual elite during the decade of reform (1977-89). He shows how the Deng Xiaoping regime precipitated a legitimacy crisis by encouraging economic reform while preventing political reform: By departing from the economic guidelines of Maoism, the leadership undermined the basis of its own authority. Justifying this policy in the eyes of both the ruling political elite and the increasingly powerful intellectual elite proved increasingly difficult. In addition to demonstrating the role intellectuals played in shaking Communist-party rule, the book offers a theoretical model to explain how they were able to do so. The author's concept of "institutional parasitism" depicts how, rather than developing separate institutions, resistance to the ruling political elite occupied state structures from which oppositional activity was carried out. In challenging the state versus civil society model, this book makes an important contribution to understanding changing state-society relations in late communism, and the dynamics of the transition from communism. It will be of interest to both scholars of China and students of comparative communism.